Magnetic Resonance Imaging in Autism Spectrum Disorders: clinical and neuroradiological phenotypes - Pizzolorusso, Francesco; Paparella, Maria Teresa; Pizzolorusso, Ilaria; Masino, Federica; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Autism Spectrum Disorders (ASDs) are a group of neurodevelopmental disorders that can severely compromise social and cognitive functions in childhood. Magnetic Resonance Imaging (MRI) currently represents the gold standard as an in vivo and non-invasive study of the human brain morphology. This work aims to search for possible links between clinical phenotypes and radiological anomalies that may be relevant and pathognomonic in the subsequent diagnosis of ASDs. Methods: This is a retrospective study in which 132 patients (112 males and 20 females) with neurodevelopment disorders, including ASDs, were enrolled. The population study was divided into three groups considering their own pathological diagnosis. All patients included in this population underwent genetic screening and one or multiple 1.5T MRI scans were performed to evaluate potential anomalies of the corpus callosum, periventricular white matter, ventricular space, cerebellum, subarachnoid space and thalamus. Results: Univariate analysis showed that the presence of MRI brain abnormalities was a significant variable in predicting the presence of ASDs. Increased ventricular volume was one of the most replicated findings in ASDs patients since it was reported to be statistically significant both in uni- and multivariate analysis, resulting even as a potentially predictive factor of diagnosis. Conclusions: This study can represent a starting point for the research of new radiological evidence that might be important to early diagnose ASDs and for making a differential diagnosis with all those conditions that mimic autistic traits, but which are not clinically connected to the spectrum disorder itself.